Reference videos reduce variability of motor dysfunction assessments in multiple sclerosis. Issue 3 (August 2018) - D'Souza, Marcus; Steinheimer, Saskia; Dorn, Jonas; Morrison, Cecily; Boisvert, Jacques; Kravalis, Kristina; Burggraaff, Jessica; van Munster, Caspar EP; Diederich, Manuela; Sellen, Abigail; Kamm, Christian P; Dahlke, Frank; et al.
Motor dysfunction, particularly ataxia, is one of the predominant clinical manifestations in patients with multiple sclerosis (MS). Assessment of motor dysfunction suffers from a high variability. We investigated whether the clinical rating of ataxia can be improved through the use of reference videos, covering the spectrum of severity degrees as defined in the Neurostatus-Expanded Disability Status Scale. Twenty-five neurologists participated. The variability of their assessments was significantly lower when reference videos were used (SD = 0.12; range = 0.40 vs SD = 0.26; range = 0.88 without reference videos; p  = 0.013). Reference videos reduced the variability of clinical assessments and may be useful tools to improve the precision and consistency in the clinical assessment of motor functions in MS.